GRADUATION STUDY WITH SPLINE INTERPOLATION IN THE CONSTRUCTION OF BPJS KESEHATAN PREVALENCE MORBIDITY TABLE SPECIALIZED CATASTROPHIC DISEASES - Virda Antami, Safira
The morbidity table contains morbidity rates by age for male and female. Generally, this table is used in determining premiums for health insurance products. The Indonesia Critical Illness Morbidity Table became Indonesia's first morbidity table published in November 2022. The construction of this morbidity table goes through 4 stages, namely: exposure calculation, claim calculation, graduation, and extrapolation. Unlike mortality tables, there has not been much development done on morbidity tables. Studies related to the use of methods at the graduation stage are one of the interesting things that can be developed. Graduation aims to smooth the empirical morbidity rate without significantly changing its value. The graduation study on the formation of the BPJS Health Prevalence Morbidity Table specifically for Catastrophic Diseases was carried out with spline interpolation. Prevalence indicates how many individuals in a population experience a particular disease. The prevalence morbidity rate is calculated by reviewing all claim events in the study year, namely 2018 - 2021. Catastrophic disease-specific morbidity rates were calculated by reviewing claims from 8 diseases, namely: heart, cancer, stroke, renal failure, hemophilia, thalassemia, leukemia, and liver cirrhosis. The spline functions used in spline interpolation are linear spline, quadratic spline, and Natural Cubic Spline (NCS). The selection of node points in spline interpolation is one of the important things in producing good graduation. By limiting the node points to a maximum of 9 points, the RMSE values of linear spline, quadratic spline, and NCS interpolation were 2,164%; 2,535%; and 1,726% for males and 1,753%; 2,388%; and 1,466% for females, respectively. NCS interpolation gave the best graduated results. Thus, the morbidity rates from the graduation results with NCS interpolation were used in the construction of the BPJS Kesehatan Prevalence Morbidity Table specifically for Catastrophic Diseases. The morbidity level in this table has values in the range of 0.010062 to 0.380740 for males and 0.000650 to 0.372211 for females.